Functionalized heterocycle-appended porphyrins: catalysis matters. Issue 69 (23rd November 2020) - Abdulaeva, Inna A.; Birin, Kirill P.; Polivanovskaia, Daria A.; Gorbunova, Yulia G.; Tsivadze, Aslan Yu
Abstract : The condensation of labile 2, 3-diaminoporphyrins with aromatic aldehydes is a versatile technique for the elaboration of functionalized porphyrins. The acidic catalyst in the reaction is a tool that allows the reaction path to be switched. Abstract : The scope and limitations of the condensation of labile 2, 3-diaminoporphyrin derivatives with aromatic aldehydes to provide functionalized imidazole- and pyrazine-appended porphyrins were investigated in detail. The presence of an acidic catalyst in the reaction was found to be a tool that allows the reaction path to be switched. The influence of the electronic origin of the substituents in the carbonyl components of the condensation on the yields and selectivity of the reaction was revealed. Metal-promoted cross-coupling transformations were found to be convenient for the further targeted construction of functional derivatives based on the prepared bromo-substituted pyrazinoporphyrins. Overall, these strategies provide a versatile technique for the elaboration of a variety of functionalized heterocycle-appended porphyrins for further application in the development of hybrid materials.